Cyclic Polymers by Ring‐Closure Strategies. Issue 45 (21st September 2016) - Josse, Thomas; De Winter, Julien; Gerbaux, Pascal; Coulembier, Olivier
Abstract: The preparation of cyclic macromolecules has always represented a challenging task for polymer science, mainly because of difficulties in connecting chain extremities together. Initiated by the pioneering studies of Jacobson and Stockmayer, preparative pathways to cyclic polymers have been considerably improved within the last two decades thanks to the advent of both controlled polymerizations and efficient coupling reactions in organic chemistry. This Review aims to provide a critical up‐to‐date overview and illustrate the considerable efforts that have been made in the past few years to improve the availability of macrocycles for industrial and academic investigations through the use of the ring‐closure approach. Particular attention is paid to methods for the preparation of monocycles over more complex architectures, since the latter are usually derived from the former. Abstract : Closing the circle : The preparation of cyclic macromolecules is challenging. Considerable improvements have been made to improve the availability of macrocycles for industrial and academia investigations through the use of ring‐closure approaches. This Review focuses on methods to prepare monocycles preferentially over more complex architectures, since the latter are usually derived from the first.